DESAIN PESAN MULTIMEDIA PEMBELAJARAN DALAM TEORI PEMROSESAN INFORMASI - Munawaroh, Isniatun (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Delivering text simultaneously in written and spoken form is common in multimedia resentations.Nevertheless, the assumption that simultaneous presentations of written and auditory text is beneficial maybe erroneous. From a theoretical perspective, it is suggested that it persons are required to coordinate and stimultaneously process redundant material are such as written and spoken text, an excessive working memory load is generated. Working memory may be overburdened if instruction involves excessiveelements of novel information processed simultancously. The common instructional procedure (particularly in multimedia instructional) of presenting identical spoken and written material simultancously may need tobe avoided.